2017
DOI: 10.1523/jneurosci.1647-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Valproic Acid Treatment Mediated by Histone Deacetylase Inhibitor Activity in Four Transgenic X. laevis Models of Retinitis Pigmentosa

Abstract: Retinitis pigmentosa (RP) is an inherited retinal degeneration (RD) that leads to blindness for which no treatment is available. RP is frequently caused by mutations in Rhodopsin; in some animal models, RD is exacerbated by light. Valproic acid (VPA) is a proposed treatment for RP and other neurodegenerative disorders, with a phase II trial for RP under way. However, the therapeutic mechanism is unclear, with minimal research supporting its use in RP. We investigated the effects of VPA on Xenopus laevis models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Likewise, VPA had opposing effects on the degeneration of rod photoreceptors in two Pde6b mutation models, the rd1 and the rd10 mouse, in which rd1 photoreceptors were protected by VPA treatment, whereas it, in contrast, accelerated the rd10 photoreceptor degeneration (Mitton et al, 2014). Similar discrepancies have been seen in other studies (Berner and Kleinman, 2016), and the use of VPA in people with RP has not resulted in a consensus on whether or not this is a valuable treatment option, or if it may actually be negative (Dias et al, 2018;Vent-Schmidt et al, 2017). The situation with HDAC involvement in RD, which as discussed above are indeed heterogenous, is thus extremely complex.…”
Section: Histone Acetylation and Deacetylationmentioning
confidence: 64%
See 1 more Smart Citation
“…Likewise, VPA had opposing effects on the degeneration of rod photoreceptors in two Pde6b mutation models, the rd1 and the rd10 mouse, in which rd1 photoreceptors were protected by VPA treatment, whereas it, in contrast, accelerated the rd10 photoreceptor degeneration (Mitton et al, 2014). Similar discrepancies have been seen in other studies (Berner and Kleinman, 2016), and the use of VPA in people with RP has not resulted in a consensus on whether or not this is a valuable treatment option, or if it may actually be negative (Dias et al, 2018;Vent-Schmidt et al, 2017). The situation with HDAC involvement in RD, which as discussed above are indeed heterogenous, is thus extremely complex.…”
Section: Histone Acetylation and Deacetylationmentioning
confidence: 64%
“…TSA was similarly able to reduce cone cell death in the cone degeneration model cpfl1 in explant culturing, and, more importantly, in vivo through intravitreal injection (Trifunovic et al, 2016). On the other hand, yet another broad HDAC inhibitor, valproic acid (VPA), exhibited either protective or detrimental effects in Xenopus laevis models of rhodopsin mutation-based RP, depending on the exact type of genetic defect (Vent-Schmidt et al, 2017). Likewise, VPA had opposing effects on the degeneration of rod photoreceptors in two Pde6b mutation models, the rd1 and the rd10 mouse, in which rd1 photoreceptors were protected by VPA treatment, whereas it, in contrast, accelerated the rd10 photoreceptor degeneration (Mitton et al, 2014).…”
Section: Histone Acetylation and Deacetylationmentioning
confidence: 99%
“…A number of previous studies have tested epigenetic modifiers as possible therapeutics for retinitis pigmentosa. Some of these have focused on the neuroprotective effects of blocking HDAC activity by such nonselective inhibitors as TSA, valproic acid (VPA), and sodium butyrate (Chuang et al, 2009;, all of which have some protective effect on RP (Mitton et al, 2014;Zhang et al, 2015;Berner and Kleinman, 2016;Todd and Zelinka, 2017;Vent-Schmidt et al, 2017). The broad-spectrum HDAC inhibitor VPA has been tested as a therapeutic agent for retinal degeneration with mixed results (Clemson et al, 2011;Kumar et al, 2014;Iraha et al, 2016;Totan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…151 Moreover, VPA was demonstrated to have a beneficial effect in an in vitro model characterized by P23H mutation of rhodopsin, while it had a detrimental effect on the degeneration of the retina in the T17 M model of RP, this latter effect seemingly due to inhibition of HDAC. 152 The role of HDAC6 in retinal degeneration was specifically investigated by Leyk et al, 153 who demonstrated that mousederived cone-like 661W cells do express HDAC6 and that the enzyme is active in that model because treatment with specific inhibitors led to α-tubulin hyperacetylation. Inhibition of HDAC6 protected the cells from oxidative stress induced by H 2 O 2 .…”
Section: Hdac6 and Inherited Retinal Diseases (Irds)mentioning
confidence: 99%